Obtenção de bacteriocinas de bactérias láticas em água residuária de indústria de fécula de mandioca - Vilvert, Raquel Minuceli (2019)
Bacteriocins are products of the metabolism of many lactic acid bacteria and have attracted interest from researchers due to their antimicrobial activity and possibility of use in food preservation and in the pharmaceutical industry. Cassava products and its processing residues are commonly related to the presence of lactic acid bacteria, therefore, those can be considered substrates for the production of bacteriocins from lactic bacteria isolated from the residue itself, thus representing a form of recovery and minimizing the environmental impact generated by these wastes. In this sense, the objective of this work was to evaluate the production of bacteriocins from lactic bacteria isolated of the cassava agroindustrial process residue. The isolation of a lactic acid bacterium from the cassava industry residue was carried out and analyzed regarding its potential for bacteriocin production. In addition, the residue water was used as a substrate for bacteriocin production. For this purpose, an experimental planning for the optimization of the production was developed, beginning with Plackett Burnam (PB) with 5 factors that could influence the production of this bacteriocin. It was observed that only 3 factors, namely, sucrose, yeast extract and magnesium sulfate, played influence on the production of Bacteriocin using wastewater as culture medium. A rotational central composite experimental design (DCCR) was employed, and for the derivation in the methodology of response surface, a statistical model of optimization of the composition of the culture medium was adopted, using waste water from corn starch industry. The bacteriocin production was evaluated in a reactor, in sequential batch, using the bacteria isolated as bacteriocin product and optimized residual water as culture medium. The reactor was monitored at every 15 hours and samples of the efluente were collected to determine bacteriocin production. The reactor was conducted for 13 cycles in condition (i) optimized residual water, according to DCCR, autoclaved (121 oC/15 min) until decrease of bacteriocin could be observed; and for 6 cycles in condition (ii) optimized residual water, according to the DCCR, without autoclaving until decrease in bacteriocin production was observed. The isolated bacterium capable of producing bacteriocin was the lactic acid bacterium Leuconostoc Mesenteroides. The results showed that the optimum culture medium for bacteriocin production was composed of sucrose 18.70 g/L yeast extract 14.60 g/L, and magnesium sulfate 1.3 g/L, and that the maximum production of bacteriocin happens in 15 hours of fermentation. When cultivated in optimum culture medium, the yield of bacteriocin is 1205.58 Au/mL. When fermentation is carried out on a larger scale, in the reactor, through sequential batch, bacteriocin levels increases up to 56.76% higher than the experimental result obtained in the optimum condition and this increase occurs only in condition (i), since (ii) Bacteriocin production occurred only after 15 hours of fermentation. Therefore, it was possible to identify the presence of lactic acid bacteria, as well as the production of bacteriocin in the wastewater of the cassava starch industry, as well as to optimize the residual water for bacteriocin production.